2009
DOI: 10.1039/b903049b
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in metal carcinogenesis: nickel, arsenic, chromium and cadmium

Abstract: SummaryAlthough carcinogenic metals have been known to disrupt a wide range of cellular processes the precise mechanism by which these exert their carcinogenic effects is not known. Over the last decade or two, studies in the field of metal carcinogenesis suggest that epigenetic mechanisms may play a role in metal-induced carcinogenesis. In this review we summarize the evidence demonstrating that exposure to carcinogenic metals such as nickel, arsenic, chromium, and cadmium can perturb DNA methylation levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
231
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 349 publications
(237 citation statements)
references
References 90 publications
(165 reference statements)
4
231
2
Order By: Relevance
“…For example, epigenetic variations among populations have been shown to be influenced by differences in geographic location, lifestyles and nutritional status [7]. Epigenetic mechanisms are influenced by heavy metal exposure [30], the latter often being a consequence of geographic location. Individuals from Nigeria, the country of origin for YRI, are more exposed to heavy metals than Europeans and Americans [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, epigenetic variations among populations have been shown to be influenced by differences in geographic location, lifestyles and nutritional status [7]. Epigenetic mechanisms are influenced by heavy metal exposure [30], the latter often being a consequence of geographic location. Individuals from Nigeria, the country of origin for YRI, are more exposed to heavy metals than Europeans and Americans [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that iAs exposure induces global and gene-specific post-translational histone modifications such as reduction of acetylation in histone H3 and H4: loss of H4Lys 16 10 and H2AX phosphorylation, and decreases in H2B ubiquitination (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…However, the effect of Cd in carcinogenesis has not been studied in relation to DNA hydroxymethylation, which would enable a better understanding of Cd exposed carcinogenesis [98]. A similar effect of heavy metals on IDH, SDH and FH inhibition may throw light on alternate 5hmC deregulation mode of carcinogenesis.…”
Section: Heavy Metals Deregulate 5-hydroxymethylcytosinementioning
confidence: 99%